Liver diseases and pregnancy - Pietro Crispino; Luca Fontanella; Paola Gnerre (Italian Journal of Medicine, 2017)
Pregnancy is a time of great maternal physiological and metabolic changes and affects biochemical and hematological parameters used in the assessment of liver disease. Due to the increased physiological and metabolic stress of pregnancy, liver disorders that have previously been subclinical may become symptomatic such as cholestatic diseases. The viral hepatitis constitutes a huge disease burden worldwide and the pregnant state confers particular concerns for the mother and her baby. In particular, hepatitis E has a predilection for the pregnant population and confers a particularly poor prognosis. In addition, certain pregnancy specific disorders such as elevated liver enzymes, low platelets syndrome, acute fatty liver of pregnancy, and obstetric cholestasis-affect primarily the liver. It is important to know how to diagnose and manage these conditions and distinguish them from non-pregnancy specific conditions as this will change the timing and management of affected women and their babies, some of whom can be seriously ill.